Effects of Chemical and Mechanical Lysis on Microbial DNA Yield, Integrity, and Downstream Amplicon Sequencing of Rumen Bacteria and Protozoa - Ma, Zhi Yuan; Zhang, Xiu Min; Wang, Rong; Wang, Min; Liu, Ting; Tan, Zhi Liang (Frontiers in Microbiology, 2020)
QIAamp Fast DNA Stool Mini Kit (Qiagen, Valencia, CA, USA) and RBB+C (Yu and Morrison, 2004) methodologies are widely employed to extract microbial DNA from rumen samples, and can exhibit different efficiencies of obtaining DNA yield, quality and downstream amplicon sequence analysis. No study has conducted to investigate the contributions of chemical and mechanical lysis on DNA extraction, which included chemical lysis from QIAamp Fast DNA Stool Mini Kit (QIA) and RBB+C (YM), bead (BB) and sand beating (SB). Effects of chemical lysis and bead beating (BB) were investigated by conducting a 2×2 factorial-designed experiment with four methodologies, including QIA without (QIA-) and with BB (QIA+BB), and YM without (YM-) and with BB (YM+BB). Comparisons between bead and sand were conducted by comparing methodologies of YM+BB and YM+SB. Comparing with QIA, YM had lower (P ≤ 0.10) OD260/280 and diversity of ZOTUs and length polymorphism of protozoal amplicons, but harvested greater (P ≤ 0.086) DNA from fibrolytic bacteria such as Ruminococcaceae lineages. Including BB increased (P = 0.001) total DNA yield without affecting (P ≥ 0.55) OD260/280 and richness of bacterial ZOTUs, but decreased (P ≤ 0.08) richness of both ZOTUs and length polymorphism of protozoal amplicon. Bead beating and SB showed no difference (P ≥ 0.19) in DNA yield and quality, bacterial and protozoal community. In summary, chemical lysis provided by RBB+C and QIAamp Fast DNA Stool Mini Kit should be better to extract DNA for analyzing bacterial and protozoal community respectively. Sand can be an alternative beater for DNA extraction, and mechanical lysis is not recommended for protozoal community analysis.